A new species of the schizomid genus Stenochrus (Schizomida: Hubbardiidae) from Mexico - Monjaraz-Ruedas, Rodrigo (Zootaxa, 2012)
A new Mexican species of Stenochrus Chamberlin, 1922. Stenochrus valdezi new species, is described from Cueva de SanFrancisco in Chiapas based on adult male and female specimens. With the description of this species, there are 17 species from Mexico, being the country with the highest diversity of species of the genus Stenochrus worldwide.